Circulating tumour DNA sequence analysis as an alternative to multiple myeloma bone marrow aspirates - Olena Kis (Nature Portfolio, 2017)
Genetic profiling of multiple myeloma requires painful bone marrow biopsies. Here, the authors develop an alternative non-invasive method for sequencing of five oncogenes in circulating cell-free DNA from myeloma patients, demonstrating 96% concordance with bone marrow tumour profiling results.